Die Krise von DaZ.: Ein Lösungsansatz zur funktionalen Bestimmung von Zweitsprache im Migrationskontext - Bongo, Giancarmine (Linguistik Online, 2025)
This article focusses on the question of the crisis in the opposition of GFL and GSL, which has once again become a relevant issue in today’s debate in the field: This crisis is attributed here to the constitutive characteristics of the category “German as a second language” itself, which can be explained from a subject-historical and acquisition-related point of view and are also appropriate in part, but which disregard essential, functional characteristics of German as a foreign language in the context of migration – primarily also in relation to the current situation and to new and more differentiated learning constellations. From a functional perspective – one could say – the second language is not defined in relation to the ‘first language’ (Erstsprache) determined by the process of language acquisition, but rather to the functional ‘first language’ (erste Sprache) determined by language use and often as such – which makes the term second language misleading. In line with Zabel et al.’s (2022: 7) proposal for a new category “German in the context of multilingualism”, a possible functional definition of second language and its categorisation in an equally functional model of multilingualism is therefore outlined.